(untitled) (International Journal of Medical and Surgical Sciences, 2015)
Zygomatic-orbital complex fractures are common in the middle face. As a protocol, it is necessary to establish an adequate exposure of the surgical site. The best surgical approach still remains a lot of controversy. However, the bicoronal flap is a versatile surgical technique to expose the craniofacial skeleton and allow an appropriate access to reduce and fix the fractured segments, being therefore a good alternative for the treatment. The association of other surgical approaches could promote better exposure of the fractured areas, turning an invasive procedure more complete and favorable. This article aims to report a case of zygomatic-orbital complex fractures and suggest a coronal approach along with others techniques to treat this kind of trauma. The great outcomes showed a satisfactory rehabilitation, fractures stabilized, favorable function and good aesthetic.